Opinions and Practices for Grammar Teaching in Primary School - BENZER, AHMET (My University, 2022)
In the research, it is aimed to address the views of primary school teachers about grammar teaching with a holistic approach. The research is a qualitative study, and a case study approach has been adopted. The study group consists of 101 primary school teachers working in Istanbul. The data were collected with a semi-structured interview form developed by the researchers, and the content analysis technique was used in the analysis of the data. According to the results of the research, it has been determined that primary school teachers have high self-efficacy perceptions of grammar teaching and they do not need in-service training. In addition, teachers state that they teach grammar in primary school, and they consider it necessary, that they need a separate lesson hour for grammar teaching, and that they experience problems arising from the abstractness of grammar subjects. They find the Turkish course book insufficient in terms of the number and scope of the subjects and activities. They think that the teacher\"s guidebook is necessary for terms of being a guide for the teacher. They use worksheets in grammar teaching, they prefer two different methods, from example to rule and from rule to example, and they use videos on digital platforms and activities in the textbook. It is recommended to prepare a grammar teaching book and a teacher\"s guidebook that will minimize the differences in practice among teachers. Other suggestions are to organize in-service courses that include grammar strategies, methods, and techniques suitable for the primary school level, and to update the Turkish lesson curriculum in line with the needs of the primary and secondary levels.
Keywords: EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Primary school; grammar teaching; functional grammar